Pengaruh Escapism, Hedonic Motivation, Dan Interaksi Sosial Terhadap Niat Beli Diamond Mobile Legends Di Kota Batam - Siti Nurlailliyah; Wasiman Wasiman (Community Engagement and Emergence Journal (CEEJ), 2026)
This study aims to analyze the influence of Escapism, Hedonic Motivation, and Social Interaction on the purchase intention of Mobile Legends Diamonds in Batam City. The study employed a quantitative research method by distributing questionnaires to Mobile Legends players who had purchased or had the potential to purchase Diamonds. The findings indicate that Escapism has a positive and significant effect on purchase intention, suggesting that players' desire to escape from daily routines encourages them to make in-game purchases. Furthermore, Hedonic Motivation was found to have a positive and significant influence, indicating that the enjoyment and emotional satisfaction derived from gameplay increase players' tendency to purchase Diamonds. Social Interaction also has a positive and significant effect on purchase intention, as social relationships within the game, teamwork, and the desire to enhance one's status within the gaming community strengthen players' motivation to make purchases. Simultaneously, these three variables significantly influence the purchase intention of Mobile Legends Diamonds. Therefore, higher levels of escapism, hedonic motivation, and social interaction are associated with a greater likelihood of purchasing Mobile Legends Diamonds. These findings provide valuable insights for game developers in designing more effective marketing strategies.